Tensile Behavior and Statistical Analysis of Washingtonia Filifera Fibers as Potential Reinforcement for Industrial Polymer Biocomposites - Isma Dembri; Ahmed Belaadi; Messaouda Boumaaza; Mostefa Bourchak (Journal of Natural Fibers, 2022)
Natural fibers continue to attract the attention of researchers because of their use in reinforced polymer composites. They allow industrial designers to find solutions to aging infrastructure problems more than 50 years after their use in aerospace, automotive, construction, consumer products, etc. These fibers are economical and low density. In fact, in addition to their specific properties, such as non-abrasiveness and biodegradability, they are an ecological material with low environmental impact. Washingtonia Filifera (WF) fiber, among others, is attracting more and more researchers to replace certain fibers such as synthetic or glass fibers, being widely used in the world. This study aims to determine the mechanical parameters of WF fibers with a gauge length (GL = 50 mm) in quasi-static tension. Tensile tests were carried out on 150 fibers in five-test series to determine the influence of their variability on the tensile stress, strain at break and Young’s modulus of plant fibers. Due to the dispersion of the results of the mechanical tensile properties of WF fibers, which is a characteristic of natural fibers, a statistical study is necessary. Thus, statistical tools such as the two and three-parameter Weibull distribution at 95% confidence level (CI) and the one-way analysis of variance ANOVA were carried out to study this dispersion.